The main sequence of star-forming galaxies – II. A non-evolving slope at the high-mass end. Issue 4 (21st September 2019) - Popesso, P; Morselli, L; Concas, A; Schreiber, C; Rodighiero, G; Cresci, G; Belli, S; Ilbert, O; Erfanianfar, G; Mancini, C; Inami, H; Dickinson, M; et al.
ABSTRACT: By using the deepest available mid- and far-infrared surveys in the CANDELS, GOODS, and COSMOS fields we study the evolution of the main sequence (MS) of star-forming galaxies (SFGs) from z ∼ 0 to ∼ 2.5 at stellar masses larger than 10 10 M⊙ . The MS slope and scatter are consistent with a rescaled version of the local relation and distribution, shifted at higher values of star formation rate (SFR) according to ∝ (1 + z ) 3.2 . The relation exhibits a bending at the high-mass end and a slightly increasing scatter as a function of the stellar mass. We show that the previously reported evolution of the MS slope, in the considered mass and redshift range, is due to a selection effect. The distribution of galaxies in the MS region at fixed stellar mass is well represented by a single lognormal distribution at all redshifts and masses, with starburst galaxies occupying the tail at high SFR.